A dual-driving piezoelectric DETF resonator with high quality factor and low multimode effect. (5th July 2018) - Liu, Xinxin; Wang, Yixiang; Le, Xianhao; Xu, Zhonggui; Wu, Changju; Xie, Jin
Abstract: A high quality factor ( Q ) piezoelectric double-ended tuning fork (DETF) resonator with dual-driving capacity based on aluminum nitride (AlN) is reported in this paper. This novel dual-driving electrode design in a piezoelectric resonator can not only enhance the symmetry in the in-plane mode but also weaken the crosstalk from the out-of-plane mode. By trapping the vibration energy in the wanted mode, the dual-driving DETF improves Q to 8173 compared to the conventional single-driving DETF with a Q of 3632. Through this dual-driving strategy, the DETF is excited to vibrate more closely with the in-plane resonant mode, which has less energy loss and balanced stress distribution. In addition, the dual-driving method also increases the signal intensity at the symmetric mode while reducing the signal intensity at the out-of-plane mode. This suppressed multimode effect contributes to a high performance of the DETF resonators and shows good potential in piezoelectric resonant sensors with high resolution.